(Un)leashed potentials: an activist-centered perspective on the political mobilization of motorcycle taxi drivers in eastern DRC - Muller, Carol (Journal of Eastern African Studies, 2024)
The re-emergence of competitive elections in Africa has sparked new interest in political mobilization on the continent. Much of this literature focusses on political actors and the strategies they use to mobilize. If the campaign activists are reviewed at all, they are often categorized by their ethnic or religious affiliation. Thereby, abilities and potentials for political participation, which are important within conceptual literature on political mobilization, are side-lined. This article uses an activist-centered perspective to review the political mobilization of motorcycle taxi drivers, eastern Congo. Based on empirical research in 2020 and 2021, it evaluates the mobilization potentials of the so-called motards and their deployment during political action. The article finds that motards possess unique potentials for participating in political campaigns due to their mobility and large social networks but only partially deploy them. While their mobility potential is widely utilized, the mobilization of their social networks is hampered by a lack of allegiances and infrequent contacts with politicians. Based on the research findings, the article advocates expanding the perception of political mobilization in Africa by reflecting on the preconditions of mobilizability such as enabling potentials, interactions with activists and aligned political strategies.
Keywords: Political mobilization; motorcycle taxis; campaign activists; Africa; D.R. Congo; Kivu